2018
DOI: 10.1172/jci96582
|View full text |Cite
|
Sign up to set email alerts
|

Increased vessel perfusion predicts the efficacy of immune checkpoint blockade

Abstract: Immune checkpoint blockade (ICB) has demonstrated curative potential in several types of cancer, but only for a small number of patients. Thus, the identification of reliable and noninvasive biomarkers for predicting ICB responsiveness is an urgent unmet need. Here, we show that ICB increased tumor vessel perfusion in treatment-sensitive EO771 and MMTV-PyVT breast tumor as well as CT26 and MCA38 colon tumor models, but not in treatment-resistant MCaP0008 and 4T1 breast tumor models. In the sensitive tumor mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
167
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(176 citation statements)
references
References 45 publications
6
167
3
Order By: Relevance
“…For example, Tian et al demonstrated that—in a preventative setting—normalized vessel formation and antitumor immune responses were reciprocally regulated by CD4 + and not CD8 + cells in an IFN‐γ‐dependent manner in breast cancer models. This contrasted with data generated in an interventional setting, where Zheng et al showed that CD8 + T‐cell activation by ICB alone mediated the normalization of tumor vessels, albeit also in an IFN‐γ‐dependent manner.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…For example, Tian et al demonstrated that—in a preventative setting—normalized vessel formation and antitumor immune responses were reciprocally regulated by CD4 + and not CD8 + cells in an IFN‐γ‐dependent manner in breast cancer models. This contrasted with data generated in an interventional setting, where Zheng et al showed that CD8 + T‐cell activation by ICB alone mediated the normalization of tumor vessels, albeit also in an IFN‐γ‐dependent manner.…”
Section: Discussioncontrasting
confidence: 75%
“…This may be because antiangiogenesis (AA) can excessively prune vessels and increase hypoxia . Interestingly, a recent study has shown that anti‐PD‐1 therapy can increase blood perfusion of tumors by normalizing vessels in breast and colorectal cancer models . However, the effect of anti‐PD‐1 therapy—alone or with anti‐VEGF/R therapy—on HCC vasculature is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). We simulate how antiangiogenic, stroma normalization, and immunotherapy treatments affect model components and compare model predictions with previous experimental studies (19,24,26,36,49). Furthermore, we use model predictions to provide guidelines for the optimal use of these three strategies and point out the gaps in our understanding.…”
mentioning
confidence: 98%
“…In addition, hypoxia and acidity affect the function of T lymphocytes and other immune cells (14)(15)(16), whereas hypoperfusion and the dense/stiff TME is a physical barrier to T cell infiltration into the tumor (17,18). Indeed, increased perfusion has been related to improved ICB response (19).…”
mentioning
confidence: 99%